An efficient synthesis of warfarin acetals on montmorillonite clay K-10 with microwaves - S. SOLUJIC; S. SUKDOLAK; LJ. KRSTIC (Journal of the Serbian Chemical Society, 2002)
The microwave promoted reaction of warfarin with methanol, or ethanol, in the presence of montmorillonite clay K-10 as a catalyst, affords the corresponding acetals, 2-methoxy-2-methyl-4-phenyl-3,4-dihydro-2H-pyrano[3,2-c]chromen-5-one (2) and 2-ethoxy-2-methyl-4-phenyl-3,4-dihydro-2H-pyrano[3,2-c]chromen-5-one (3), respectively, in good yields.